Long non-coding RNA ZFAS1 correlates with clinical progression and prognosis in cancer patients - Liu, Fangteng (Oncotarget, 2017)
Dysregulation of long non-coding RNA zinc finger antisense 1 (ZFAS1) has been reported in many types of cancers. We performed a synthetic analysis to clarify its prognostic significance as a cancer molecular-marker. Several databases (including PubMed, Web of Science, Embase together with Wanfang and China National Knowledge Internet database) were retrieved to identify ZFAS1-related articles. A total of eight articles were included in this meta-analysis. Hazard ratios (HR) and 95% confidence intervals (CI) were applied to assess the association between ZFAS1 expression level and overall survival (OS). Odds ratios (OR) were calculated with RevMan 5.3 software to determine the relationship between ZFAS1 expression and clinicopathologic features. The pooled results of the meta-analysis indicated that high ZFAS1 expression level was positively correlated with poor OS (HR = 1.87, 95% CI: 1.38-2.36, p< 0.001) in human solid cancers. The statistical significance was also observed in subgroup analysis stratified by the cancer type, analysis method, sample size and follow-up time. Furthermore, the elevated ZFAS1 expression was significantly related to positive lymph node metastasis (OR = 4.18, 95% CI: 2.70-6.48, p< 0.001). The present results suggest that ZFAS1 might be served as a novel promising biomarker for prognosis in Chinese patients with solid cancers.